Glycation of Human Serum Albumin in Diabetes: Impacts on the Structure and Function - Cao, Hui; Chen, Tingting; Shi, Yujun (Current Medicinal Chemistry, 2015)
Diabetes mellitus is one of the most serious diseases in the world. The levels of glycated proteins in the blood of diabetics are higher than that of non-diabetic subjects. The glycation of proteins is believed to link to the occurrence of diabetic complications and related diseases. This review focuses on the influence of glycation of human serum albumin (HSA) on its structure and function. The glycation leads to change the HSA conformation, which will further influence its ligand binding properties. The levels of glycated HSA in hyperglycemic conditions showed a significant relationship to the germination of serious complications for diabetics, especially by affecting various cells functions. The conclusion from individual report is contradictory to each other; therefore, it is very difficult to give an univocal comment on the impact of glycation on the binding behaviors of HSA for small molecules. The influence of glycation of HSA on the binding affinities for small molecules is decided by the assay, the structures of small molecules, as well as the degree of glycation. However, the glycation of HSA is believed to reduce the binding affinities for acidic drugs such as polyphenols and phenolic acids.
Keywords: glycation